Pengaruh Profitabilitas, Leverage, dan Tata Kelola Perusahaan terhadap Tax Avoidance: Studi Empiris Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Widia Anisa Putri; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of profitability, leverage, and corporate governance on tax avoidance. This study used the secondary data obtained from the annual report of mining companies listed on the Indonesia Sock Exchange from 2017 to 2021. Sample was selected by purposive sampling technique, using some criteria and resulted 19 companies. Data was analysis by multiple linear regression analysis models. The results of this study showed that profitability, leverage, and the element of corporate governance of institutional ownership have a significant positive effect on tax avoidance as measured using proxy effective tax rate. Meanwhile, the elements of corporate governance of audit committee and audit quality have no significant effect on tax avoidance as measured using proxy effective tax rate.